Chemoradiotherapy in a patient with locally advanced small cell neuroendocrine carcinoma of the cervix complicated by pelvic organ prolapse: A case report - Luisa E. Jacomina; Michelle D. Garcia; Andrea C. Santiago; Irene M. Tagayuna; Warren R. Bacorro (Elsevier, 2021)
Background: The coexistence of cervical cancer and pelvic organ prolapse represents a rare clinical scenario. Small cell neuroendocrine histology likewise represents only 0.9-1.5% of all invasive cervical cancers. There is no consensus regarding the optimal management of patients with concomitant locally advanced cervical cancer and pelvic organ prolapse. Case summary: The patient was a 32-year old woman with an 8-cm fungating cervical mass extruding from the introitus. Biopsy was consistent with small cell neuroendocrine carcinoma. Examination showed stage IIIC1r cervical cancer with stage IV pelvic organ prolapse. After manual reduction, a pessary was used to optimize target volume reproducibility during definitive chemoradiation. The patient was treated using cisplatin and etoposide chemotherapy with intensity modulated radiation therapy followed by intracavitary brachytherapy. The patient had no clinical evidence of disease and recurrence of symptomatic prolapse one year after treatment completion. Conclusion: This is the first reported case of a cervical neuroendocrine carcinoma in a prolapsed uterus, and the youngest patient in literature to have concomitant cervical cancer and pelvic organ prolapse. The use of a pessary for optimizing target volume reproducibility during definitive chemoradiation is a viable option in managing this rare case scenario.